SENSITIVITAS Escherichia coli PENGHASIL EXTENDED SPECTRUM BETA LACTAMASE (ESBL) TERHADAP ANTIBIOTIK KELAS KARBAPENEM DARI ISOLAT KLINIS KOLEKSI BAGIAN MIKROBIOLOGI FK UGM PERIODE APRIL-SEPTEMBER 2013 - , DIAN NINA ARIFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Abstract : Bacterial resistance to antibiotics is the main problem in health. Hydrolysis of beta lactam antibiotics by beta lactamase is the most common underlying mechanism of gram negative bacterial resistance to beta lactam antibiotics. The overuse of new generation antibiotics which is especially designed for resistant to hydrolysis action by beta lactamase cause the emergence of ESBL. ESBL is an enzyme from bacteria that can make them resistant to these antibiotics. This research is done to understand the sensitivity of E.coli producing ESBL and the proportion of E.coli producing ESBL. Method : This research use descriptive method. Detection of ESBL is done with diffusion method and D68C Mast GroupÂ® test. Antimicrobial susceptibility test is done with Kirby Bauer method. Result : Out of 25 samples, 7 is detected positive producing ESBL (28%). Antimicrobial susceptibility tests show E.coli producing ESBL 42,8% sensitive and 42,8% intermediate to doripenem, 57,1% sensitive and 42,8% intermediate to ertapenem, 100% sensitive to imipenem, and 71,4% sensitive to meropenem. Conclusion : E.coli producing ESBL sensitive to karbapenem antibiotics.